Frontotemporal phase lag index correlates with seizure severity in patients with temporal lobe epilepsy - Mao, Lingyan; Zheng, Gaoxing; Cai, Yang; Luo, Wenyi; Zhang, Qianqian; Peng, Weifeng; Ding, Jing; Wang, Xin (Frontiers in Neurology, 2022)
Objectives: To find the brain network indicators correlated with the seizure severity in temporal lobe epilepsy (TLE) by graph theory analysis. Methods: We enrolled 151 TLE patients and 36 age- and sex-matched controls with video-EEG monitoring. The 90-second interictal EEG data were acquired. We adopted a network analyzing pipeline based on graph theory to quantify and localize their functional networks, including weighted classical network, minimum spanning tree, community structure, and LORETA. The seizure severities were evaluated using the seizure frequency, drug-resistant epilepsy (DRE), and VA-2 scores. Results: Our network analysis pipeline showed ipsilateral frontotemporal activation in TLE patients. The frontotemporal phase lag index (PLI) values increased in theta band (4–7 Hz), which were elevated in patients with higher seizure severities (P < 0.05). Multivariate linear regression analysis showed the VA-2 scores were independently correlated to frontotemporal PLI values in theta band (β = 0.259, P = 0.001) and age of onset (β = -0.215, P = 0.007). Significance: This study illustrated the frontotemporal PLI in theta band independently correlated to seizure severity in TLE patients. Our network analysis provided an accessible approach to and guide the treatment strategy in routine clinical practice.